Baroreflex effectiveness index: an additional measure of baroreflex control of heart rate in daily life - Di Rienzo, Marco; Parati, Gianfranco; Castiglioni, Paolo; Tordi, Roberto; Mancia, Giuseppe; Pedotti, Antonio (American journal of physiology. Regulatory, integrative and comparative physiology, 2001)
In healthy subjects, progressive beat-to-beat increases or decreases in systolic blood pressure (SBP) ramps are not always accompanied by baroreflex-driven lengthening or shortening in pulse interval (PI) ramps, respectively. This phenomenon has been quantified by a new index, the baroreflex effectiveness index (BEI), defined as the ratio between the number of SBP ramps followed by the respective reflex PI ramps and the total number of SBP ramps observed in a given time window. Specificity of BEI was shown in eight cats by a −89% reduction of BEI after sinoaortic denervation. In 14 healthy humans, the 24-h average BEI value was 0.21, with a marked day-night modulation (≈0.25 day, ≈0.15 night) in counterphase with modulation of baroreflex sensitivity (BRS). Our analysis indicates that 1) in normal subjects, arterial baroreflex can induce beat-by-beat PI changes in response to only 21% of all SBP ramps, possibly because of central inhibitory influences or of interferences at sinus node level by nonbaroreflex mechanisms and 2) BEI provides information on the baroreflex function that is complementary to BRS.